2003
DOI: 10.1114/1.1584683
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Time-Varying Identification Algorithm Using Basis Functions

Abstract: We extend a recently developed time invariant (TIV) model order search criterion named the optimal parameter search algorithm (OPS) for identification of time varying (TV) autoregressive (AR) and autoregressive moving average (ARMA) models. Using the TV algorithm is facilitated by the fact that expanding each TV coefficient onto a finite set of basis sequences permits TV parameters to become TIV. Taking advantage of this TIV feature of expansion parameters exploits the features of the OPS, which has been shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 12 publications
1
68
0
Order By: Relevance
“…The new computational techniques make the notch easier to see and study, R. Zou et al allowing future application to animal models of pathophysiological conditions and human clinical data. The effectiveness of algorithms of TVTF involved in the study has been confirmed by both simulation signals and real signals 32,48,50 (see Appendix F). …”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The new computational techniques make the notch easier to see and study, R. Zou et al allowing future application to animal models of pathophysiological conditions and human clinical data. The effectiveness of algorithms of TVTF involved in the study has been confirmed by both simulation signals and real signals 32,48,50 (see Appendix F). …”
mentioning
confidence: 67%
“…32,[46][47][48][49][50] The technical advantage of TVTF derived from ARMA modeling introduced in the study is 3-fold: 1) a parametric method to derive the transfer function from ARMA, which allows characterization of system dynamics with only a few parameters; 2) the OPS algorithm ensures an accurate estimation of transfer function, with estimated ICPs following the measured data well and prediction error consistently low (Fig. 10); and 3) with the sliding window approach a 3D TVTF (consisting of time, frequency, and gain [or phase]) can be used to visualize the dynamic response of the intracranial system to changes in mean ICP.…”
Section: Appendix F: Technical Advantagesmentioning
confidence: 99%
“…6,14 Adopting the robust OPS method, the aforementioned limitations of the previously used AR method for extraction of respiratory rate can be mitigated. Thus, the goal of this work was to investigate the efficiency gained by using the OPS instead of the AIC for extraction of respiratory rates from pulse oximeter recordings of 23 human subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Recursive algorithms such as recursive least squares (RLS), recursive instrumental variable and recursive predictive error [3,4] have also been widely investigated. For the class of rapidly time-varying systems, the functional expansion techniques have been suggested in manifold works [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Recursive algorithms such as recursive least squares (RLS), recursive instrumental variable and recursive predictive error [3,4] have also been widely investigated. For the class of rapidly time-varying systems, the functional expansion techniques have been suggested in manifold works [5][6][7][8].In [9][10][11][12], efforts have been undertaken to extend the subspace identification approach [13] to the LTV case by introducing the idea of repeated experiments. As pointed in [14], most subspace-based results developed thus far, even if significant, give state space realizations that are topologically equivalent from an input and output standpoint, but are not n Corresponding author.…”
mentioning
confidence: 99%